Gender Differences in the Allocation of Assets in Retirement Savings Plans - Sundén, Annika; Surette, Brian J. (American Economic Review, 1998)
In 1995, 40 percent of working men and 32 percent of working women were covered by a defined contribution (DC) plan. A distinguishing characteristic of these plans is that workers can generally choose how their assets are invested. Using data from the 1992 and 1995 Surveys of Consumer Finances (SCF), this paper examines whether workers differ systematically by gender in the allocation of assets in DC plans. Previous researchers have reported that many workers tend to invest their retirement assets too conservatively, and in particular that women are less likely than men to invest in risky assets such as stocks. In the presence of an equity premium, a lower propensity by women to invest in stocks could translate into large differences in the accumulation of financial wealth for retirement. We establish that gender differences in investment decisions exist, though they are more complicated than previous studies have suggested. We show that these differences are not completely explained by differences in individual or household characteristics. A few studies have examined gender differences in investment decisions (Vickie L. Bajtelsmit and Jack L. VanDerhei, 1997; Richard P. Hinz et al., 1997). These studies use administrative data and report that women tend to invest their retirement funds in less risky vehicles than men. Michael Haliassos and Carol C. Bertaut (1995) use the 1983 SCF to examine why such a large fraction of households do not own any stock. They report that gender does not have a significant effect on the probability of owning stock, though gender differences are not the focus of their paper. What these data sources lack (Haliassos and Bertaut being the exception) is a rich set of demographic and other variables on households that theory predicts should affect investment behavior. This paper adds to the literature by examining gender differences in investment decisions conditioning on such variables. The results highlight the importance of including marital status, risk-aversion measures, and the portfolio of assets held outside DC plans when examining gender differences in investment decisions in these plans.